Study of the glass fibres and internal lubricants influence in a polyamide 66 matrix on the wear evolution of polyacetal and polyamide 66 based gears in a meshing process. (April 2022) - Hriberšek, M.; Kulovec, Simon
Highlights: Flank wear characterization of POM and PA66 gears using a 3D optical microscope. Glass fibres have a positive impact on durability under higher loads. Wear rate is closely related to the contact gear temperature. Wear coefficients show that wear is inversely proportional to durability. POM gears obtained higher wear coefficients compared to PA66 based materials. Abstract: When designing gear systems, it is crucial to select materials to meet functional requirements of the application. It is necessary to know characteristics of the materials that will be integrated into drive components of the entire system to ensure a precise calculation of the system. In gear applications, system performance does not depend on a single material, but on material pairs that form a gear system. Therefore, it is desirable to test gears of different polymer materials to obtain relevant information regarding material data which are integrated into advanced virtual models to optimize mechanical structure. Gears are usually exposed to cyclic fatigue spectrum load, which causes degradation of the tooth flanks shape, and consequently increased teeth flanks wear, which results in lower load-carrying capacity. In this paper, wear behavior of gear pairs POM-PA66 and POM-PA66 reinforced with 30% of glass fibres with internal lubricants (PTFE and silicone oil) are analyzed and discussed considering load conditions. The results showed higher wear rate on the POM gears in comparison to PA66 based gears. It has been deduced that wear progression is nearly connected to more elastic material properties related with higher elongation and coefficient of linear thermal expansion for POM material in comparison to to PA based materials. Wear coefficients for POM and PA based materials imply that wear and deformation of gears are inversely proportional with durability. When observing materials at higher loads, it can be noticed that POM/PA66 GF30 TF15 Si has longer lifetime compared to POM/PA66 and vice versa at lower load. The authors concluded that lower wear and deformation of gear teeth have a decisive influence on good durability performance of gears.